Autoimmunity in the pathogenesis of severe dengue / Nurhafiza Zainal - Nurhafiza, Zainal (2018)
Dengue, an arboviral disease is transmitted between humans by the bite of infected female Aedes mosquitoes. Annually, about 50 million cases of dengue virus (DENV) infections were reported with approximately 500,000 cases of severe dengue and about 5% fatality rate. Understanding the mechanism leading to dengue or severe dengue is crucial, considering the fact that it is not completely comprehended. Autoimmunity has known to be involved in the pathogenesis of dengue. Here, we investigated the association of dengue and autoimmunity by comparing the genetic variant distribution among severe, non-severe dengue and systemic lupus erythematosus (SLE) patients using Ion Torrent sequencing method. Four significant variants were identified; novel variant at chr3:49679737 of BSN gene was associated with susceptibility to severe dengue, while polymorphisms rs76018112 of ABCF1 gene, rs1557370 of Mx1 gene and rs945635 of FCRL3 were associated with protective effects against severe dengue. Theoretical analysis on the effects of novel variant (chr3:49679737) suggests the importance of calcium release in the prevention of severe manifestation, whereas rs76018112, rs1557370 and rs945635 demonstrated that effective early antiviral responses and faster virus clearance associated with protective effects against severe dengue manifestation. SLE patients showed high distribution of all variants related to protection against severe dengue, suggesting that autoimmune disease patients might possess protective factors against acute dengue. We then analysed the protective factor of autoimmunity against dengue by determining the capability of SLE-sera to neutralize DENV using foci reduction neutralization test (FRNT). A total of 82 dengue serology negative sera of SLE patients were collected and FRNT against DENV was performed. Results revealed that 69%, 61% and 52% of the SLE patients’ sera showed FRNT50 neutralization against DENV1, DENV2 and DENV3, respectively. SLE-sera significantly neutralized DENV iv in comparison to healthy donors, though tested negative for dengue IgG/IgM antibodies, signifying that SLE patient might have an efficient antiviral response against DENV, perhaps via other antibody isotypes or autoreactive antibodies. We further investigated the association of dengue and autoimmunity by observing the role of high mobility group box 1 (HMGB1), a DNA-binding protein commonly linked to the progression of autoimmune diseases, in the pathogenesis of dengue. HMGB1 resides in the nucleus, but translocated out to the cytoplasm and extracellular milieu during DENV infection. HMGB1-knockdown cells showed higher DENV replication and lower interferonstimulated genes (ISGs) production than wild-type cells, proposing the novel role of HMGB1 in the antiviral response against DENV, through the regulation of innate immune response. Resveratrol (RESV) treatment inhibits the translocation of HMGB1 via Sirt1, and the accumulation of nuclear HMGB1 consequently increased production of ISGs and reduced DENV replication, verifying the role of nuclear HMGB1 in regulating ISGs in the antiviral response against DENV. Nuclear HMGB1 was found to bind to the promoter region of ISG and positively regulated the expression of ISGs. Our findings highlighted the importance of efficient early antiviral responses and protective effects of autoimmunity against severe dengue progression. We also introduce the novel role of nuclear HMGB1 in the antiviral response and RESV as an antiviral drug against DENV.